Enzymatic activity of bone markers on Lithobates catesbeianus (Shaw, 1802) growth during the ossification process - Colosio, R. R. [UNESP]; Santos, L. F. J. [UNESP]; Gonçalves, A. M. [UNESP]; Santana, C. C. [UNESP]; Pavarina, G. C. [UNESP]; Pizauro, J. M. [UNESP] (Instituto Internacional de Ecologia, 2021)
In order to better understand the ossification processes in anurans our study was carried out on tadpoles and adults of Lithobates catesbeianus. In this sense, we characterized the kinetic properties of alkaline phosphatase with p-nitrophenylphosphatase (pNPP) and pyrophosphate (PPi) and evaluated the activities of tartrate-resistant acid phosphatase and acid phosphatase. The enzyme extracts were obtained from tadpoles and adult femurs, which were divided into epiphysis and diaphysis. After homogenization, the samples were submitted to differential centrifugation to obtain cell membranes and, further, to phospholipase C (PIPLC) treatment, to remove membrane-bound proteins anchored by phosphatidylinositol. The average of specific activity for pNPP hydrolysis (at pH 10.5) by alkaline phosphatase released by phosphatidylinositol-specific phospholipase C (PIPLC) from Bacillus cereus among different bone regions at different animal ages was 1,142.57 U.mg-1, while for PPi hydrolysis (at pH 8.0), it was 1,433.82 U.mg-1. Among the compounds tested for enzymatic activity, the one that influenced the most was EDTA, with approximately 67% of inhibition for pNPPase activity and 77% for PPase activity. In the case of kinetic parameters, the enzyme showed a “Michaelian” behavior for pNPP and PPi hydrolysis. The Km value was around 0.6mM for pNPPase activity and ranged from 0.01 to 0.11mM for PPase activity, indicating that the enzyme has a higher affinity for this substrate. The study of pNPP and PPi hydrolysis by the enzyme revealed that the optimum pH of actuation for pNPP was 10.5, while for PPi, which is considered the true substrate of alkaline phosphatase, was 8.0, close to the physiological value. The results show that regardless of the ossification type that occurs, the same enzyme or isoenzymes act on the different bone regions and different life stages of anurans. The similarity of the results of studies with other vertebrates shows that anurans can be considered excellent animal models for the study of biological calcification.

Para melhor compreender o processo de ossificação em anuros, nosso estudo foi conduzido em girinos e adultos de Lithobates catesbeianus. Nesse sentido, as propriedades cinéticas da fosfatase alcalina com p-nitrofenilfosfato (pNPP) e pirofosfato (PPi) foram caracterizadas, e as atividades enzimáticas das fosfatases ácida e ácida tartarato resistente foram avaliadas. Os extratos enzimáticos foram obtidos de fêmur de girinos e adultos, divididos em epífise e diáfise. Após a homogeneização as amostras foram submetidas à centrifugação diferencial para obter membrana celular e, em seguida, ao tratamento com fosfolipase C (PIPLC), para remover as proteínas de membrana ancoradas por fosfatidilinositol. A média da atividade específica da fosfatase alcalina, liberada pela PIPLC de Bacillus cereus, para a hidrólise de pNPP (pH 10,5) nas diferentes regiões do fêmur e idades dos animais foi de 1.142,57 U.mg-1, enquanto para a hidrólise do PPi (pH 8,0) foi de 1.433,82 U.mg-1. Entre os compostos testados para a atividade enzimática, o de maior influência foi o EDTA, inibindo aproximadamente 67% e 77% das atividades de pNPPase e PPase, respectivamente. Quanto aos parâmetros cinéticos, a enzima apresentou comportamento Michaeliano para a hidrólise dos dois substratos. O valor de Km foi de 0,6 mM para a atividade de pNPPase e variou de 0,01 a 0,11 para a atividade de PPase, indicando uma maior afinidade por esse substrato. O estudo da hidrólise de pNPP e PPi revelou que o pH ótimo aparente de atuação foi de 10,5 para o pNPP e 8,0 para o PPi, próximo ao fisiológico, sendo que esse é considerado o substrato natural da fosfatase alcalina. Os resultados demonstram que, apesar do tipo de ossificação que ocorre, a mesma enzima ou isoenzimas, atuam nos diferentes locais do osso e estágios de vida dos anuros. A similaridade dos estudos com os realizados com outros vertebrados apontam que os anuros podem ser considerados excelentes modelos animais para o estudo da calcificação biológica.
Atividade enzimática de marcadores ósseos no crescimento de Lithobates catesbeianus (Shaw, 1802) durante o processo de ossificação
Keywords: anura; biological calcification; metamorphosis; phosphatases; kinect characterization; anura; calcificação biológica; metamorfose; fosfatases; caracterização cinética